Contribution of nitrate sources in surface water in multiple land use areas by combining isotopes and a Bayesian isotope mixing model - Jin, Zanfang; Zheng, Qi; Zhu, Chenyang; Wang, Yan; Cen, Jiarong; Li, Feili (Applied geochemistry, 2018)
Nitrate pollution is a worldwide problem in aquatic systems. Major ions and stable isotopes (δD-H2O, δ18O-H2O, δ15N-NO3 and δ18O-NO3) were applied to reveal the characteristics of nitrate and identify its sources in the East Tiaoxi River system, which is one of the most densely populated, rapidly developing and extensive crop-growing areas with multiple land uses in East China. The total nitrogen (TN) concentrations, which are dominated by nitrate (NO3−) in all of the water samples, exceed the Chinese surface water limit of 0.5 mg N L−1. The NO3− concentrations, which ranged from 0.03 to 5.46 mg N L−1, were spatially heterogeneous and were greatly affected by the hydrogeology and land uses. The temporal distribution of the NO3− concentrations (July, 1.38 ± 0.63 mg N L−1 and January, 2.77 ± 0.77 mg N L−1) was influenced by the temporal variations of precipitation. The δ15N-NO3 values ranged from +1.8‰ to +14.0‰ and the δ18O-NO3 values ranged from +3.0‰ to +11.5‰ in the East Tiaoxi River system. It was revealed that nitrification rather than denitrification acted as the primary N cycling process in the East Tiaoxi River system. The source apportionment results obtained by applying a Bayesian model (stable isotope analysis in R, SIAR) showed that there were no obvious differences in the source contributions between July and January. The source contributions differed significantly among the three reaches: soil nitrogen (68–73%) contributed more than precipitation in the upper reach, sewage/manure > chemical fertilizers > soil nitrogen contributed more than 85% of the NO3− to water in the middle reach, and chemical fertilizers > sewage/manure > soil nitrogen played the role of the major contributors (more than 85%) in the lower reach. The results indicated that nitrogen pollution causing by non-point source pollution has become a very serious problem, better nitrogen management practices should be adopted to meet safe drinking water demands and control the eutrophication in the East Tiaoxi River system. [Display omitted] •Nitrate revealed temporal and spatial variations in East Tiaoxi River system.•Chemical and isotopic characteristics were used for nitrate source identification.•A Bayesian isotope mixing model was applied in a multiple land use areas.